(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article discusses the importance of the idea of tolerance in the development and progress of countries, and, conversely, its role as a hindrance to development, the fact that interethnic harmony and religious tolerance have become a social phenomenon in Uzbekistan, and the work done in this regard.